2013
DOI: 10.1186/1749-799x-8-2
|View full text |Cite
|
Sign up to set email alerts
|

Posterolateral inter-transverse lumbar fusion in a mouse model

Abstract: BackgroundSpinal fusion is a common orthopaedic procedure that has been previously modeled using canine, lapine, and rodent subjects. Despite the increasing availability of genetically modified mouse strains, murine models have only been infrequently described.PurposeTo present an efficient and minimally traumatic procedure for achieving spinal fusion in a mouse model and determine the optimal rhBMP-2 dose to achieve sufficient fusion mass.MethodMicroCT reconstructions of the unfused mouse spine and human spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Posterolateral inter‐transverse spine fusion surgery was performed on 32 mice and, consistent with prior applications of the model, there were no cases of morbidity or mortality. Two surgeons working in tandem were able to complete an operation in ∼20 min.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Posterolateral inter‐transverse spine fusion surgery was performed on 32 mice and, consistent with prior applications of the model, there were no cases of morbidity or mortality. Two surgeons working in tandem were able to complete an operation in ∼20 min.…”
Section: Resultsmentioning
confidence: 74%
“…Although an Nf1 +/− mouse model has been previously studied in the context of tibial fracture repair, investigation of spine fusion therapies has been limited by the unavailability of a suitable model of posterolateral spine fusion. We have previously described a novel approach for mouse lumbar spine fusion that is safe, efficient, highly reproducible, and analogous to contemporary human surgery . By applying this model to Nf1 +/− we have demonstrated that dual treatment with rhBMP‐2 and ZA is superior to treatment with rhBMP‐2 alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the ectopic bone formation model, uniform discs manufactured using a surgical tissue punch were surgically implanted into the hind limbs of mice using published methods (25). For the spine fusion model, twin porous collagen sponges (Medronic Australasia) were inserted parallel to the vertebrae as previously described (26). All mice were aged 8–12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…A published method for inducing scoliosis is to encourage rodents to become bipedal by amputating their tail and elevating their food, however many researchers find this model difficult to ethically justify. Spinal fusion models are possible to create in rodents, however the differing anatomy of their spinal processes requires modification of the procedure to fuse adjacent articular processes rather than transverse processes . Such fusion models are commonly performed using both bone graft and BMPs.…”
Section: Orthopedic and Bone Tissue Engineering Modelsmentioning
confidence: 99%